Analysis of Intellectual, Emotional, Spiritual Intelligence and Interpersonal Communication on Organizational Culture as Mediating Variables (Case Study of PT. Bank Syariah Indonesia Branch Office Merdeka 3 Lhokseumawe City) - Hasibuan, Ahmad Fauzul Hakim; kharisma, Kharisma; Ichsan, Ichsan; Lestari, Lestari (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to analyze the influence of intellectual, emotional, spiritual intelligence and interpersonal communication on employee performance by considering the mediating role of organizational culture. Intellectual, emotional, spiritual intelligence and interpersonal communication are very important to instill in every employee. Where it is important for employees to decide on something to do and build good relationships with other employees or customers to grow their self-image in the work environment and the company's image in the eyes of the public. The results of this research show that intellectual intelligence influences employee performance, interpersonal communication influences employee performance. Apart from that, organizational culture does not mediate the influence of intellectual intelligence on employee performance. This shows that employees have self-confidence in solving problems and communicating well to establish working relationships with other employees or customers. And organizational culture has not been able to mediate intellectual intelligence, emotional spirituality and interpersonal communication on employee performance.